Impacto social de los medios televisivos Caravana TV y TV Oro en el comportamiento de la teleaudiencia de la Parroquia Puerto Bolívar del Cantón Machala, generado por la difusión de noticias en sus Programas Informativos, durante el primer semestre del año 2012. - Macas Castillo, Carlos Javier (2012)
This study addresses the issue of television that low motivation is one of the media of greater social impact on humans, being well used that the powerful educational tool, however, much of the information is transmitted is neither healthy nor educational. There are programs that do not contribute to strengthening the conduct and intelligence to contain high doses of violence, sex, tragedy and death. Hence arises the need to know what the press coverage, the level of training of journalists, the news that the news on TV and TV Gold Caravan spread .